Natural Clearance of Prolonged VDPV Infection in a Child With Primary Immunodeficiency Disorder - Mohanty, Madhu Chhanda; Madkaikar, Manisha Ranjan; Desai, Mukesh; Aluri, Jahnavi; Varose, Swapnil Yashwant; Taur, Prasad; Sharma, Deepa Kailash; Nalavade, Uma Prajwal; Rane, Sneha Vijay; Gupta, Maya; Shabarish, Snehal; Dalvi, Aparna; et al. (Frontiers in Immunology, 2019)
The emergence of immunodeficiency associated vaccine-derived polioviruses (iVDPV) from the children with primary immunodeficiency disorders poses a threat to the eradication program. Herein we report a patient with severe combined immunodeficiency (SCID), identified as a prolonged serotype 3 VDPV (VDPV3) excreter with thirteen VDPV3 isolates and maximum of 10.33% nucleotide divergence, who abruptly cleared infection after a period of two years. Occurrence of an episode of Norovirus diarrhea associated with increased activated oligoclonal cytotoxic T cells, inverse CD4:CD8 ratio, significantly elevated pro-inflammatory cytokines and subsequent clearance of the poliovirus suggests a possible link between inflammatory diarrheal illness and clearance of iVDPV. Our findings suggest that in the absence of B cells and sufficiently activated T/NK cells, macrophages and other T cells may produce auto-inflammatory conditions by TLR/RLR ligands expressed by previous/ ongoing bacterial or viral infections to clear VDPV infection. The study highlights the need of screening all the patients with combined immunodeficiency for poliovirus excretion and intermittent follow-up of their immune parameters if found positive, in order to manage the risk of iVDPV excretion in the polio eradication endgame strategy.